It’s Not Just a Pay Gap: Quantifying the Gender Wage and Pension Gap at a Post-Secondary Institution in Canada - Smith-Carrier, Tracy; Penner, Marcie; Cecala, Aaron; Agócs, Carol (Canadian Journal of Higher Education, 2021)
What is the impact of the gender pay gap in academia over the course of a career and retirement? To quantify this impact, we used a Canadian post-secondary institution as a case study and simulated the effects of the reported difference in salary across multiple academic career trajectories. A starting wage gap of less than 9,000 resulted in a 300,000–400,000 gender wage gap over the course of a career, and a further 148,000–259,000 gender pension gap, for a total gender pension and wage gap of 454,000–660,000, depending on the rank achieved. Thus, focusing on gender gaps in salary alone leads to a substantial underestimation of the long-term effects of the gender gap.